Embryotoxicity testing of IVF disposables: how do manufacturers test?. Issue 2 (13th February 2020) - Delaroche, L; Oger, P; Genauzeau, E; Meicler, P; Lamazou, F; Dupont, C; Humaidan, P
Abstract: STUDY QUESTION: How do manufacturers perform embryotoxicity testing in their quality control programs when validating IVF consumables? SUMMARY ANSWER: The Mouse Embryo Assay (MEA) and Human Sperm Survival Assay (HSSA) used for IVF disposables differed from one manufacturer to another. WHAT IS KNOWN ALREADY: Many components used in IVF laboratories, such as culture media and disposable consumables, may negatively impact human embryonic development. STUDY DESIGN, SIZE, DURATION: Through a questionnaire-based survey, the main manufacturers of IVF disposable devices were contacted during the period November to December 2018 to compare the methodology of the MEA and HSSA. We focused on catheters for embryo transfer, catheters for insemination, straws, serological pipettes, culture dishes and puncture needles used in the ART procedures. PARTICIPANTS/MATERIALS, SETTING, METHODS: We approached the manufacturers of IVF disposables and asked for details about methodology of the MEA and HSSA performed for toxicity testing of their IVF disposable devices. All specific parameters like mouse strains, number of embryos used, culture conditions (media, temperature, atmosphere), extraction protocol, subcontracting, and thresholds were registered and compared between companies. MAIN RESULTS AND THE ROLE OF CHANCE: Twenty-one companies were approached, of which only 11 answered the questionnaire. Significant differences existed in the methodologies and thresholds of the MEA and HSSA used for toxicity testing of IVF disposables. Importantly, some of these parameters could influence the sensitivity of the tests. LIMITATIONS, REASONS FOR CAUTION: Although we approached the main IVF manufacturers, the response rate was relatively low. WIDER IMPLICATIONS OF THE FINDINGS: Our study confirms the high degree of heterogeneity of the embryotoxicity tests performed by manufacturers when validating their IVF disposable devices. Currently, no regulations exist on this issue. Professionals should call for and request standardization and a future higher degree of transparency as regards embryotoxicity testing from supplying companies; moreover, companies should be urged to provide the users clear and precise information about the results of their tests and how testing was performed. Future recommendations are urgently awaited to improve the sensitivity and reproducibility of embryotoxicity assays over time. STUDY FUNDING/COMPETING INTEREST(S): This study did not receive any funding. L.D. declares a competing interest with Patrick Choay SAS. TRIAL REGISTRATION NUMBER: N/A